Pengaruh Efektivitas, Manfaat dan Gaya Hidup terhadap Minat Penggunaan E-Wallet pada Kalangan Mahasiswa Akuntansi UPN “Veteran” Jawa Timur dengan Pendekatan Technology Acceptance Model - Danty Aulia Rachmawati; Sri Trisnaningsih (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This study aims to test and analyze the effect of effectiveness, benefits and lifestyle on interest in using e-wallets among accounting students of UPN "Veteran" East Java with the Technology Acceptance Model approach. This type of research is quantitative research. The population of this study were accounting students of UPN "Veteran" East Java in the 2019-2021 batch of 90 respondents. The data used is primary data by distributing questionnaires via google forms. The sampling technique in this study was Probability Sampling. The analysis technique used is multiple regression analysis with the help of the Statistical Product Service Solutions (SPSS 25) program. The results of this study indicate that the effect of effectiveness has a negative and insignificant effect on interest in using e-wallets, while the effect of benefits and lifestyle has a positive and significant effect on interest in using e-wallets. Keywords: Effectiveness, Lifestyle, Benefits, Interest in Using E-Wallet